AI-Based Hotel Front Office Training Application Game Concept for Hospitality Students - Raharjo, Tito Pandu; Roedavan, Rickman (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
The advancement of Artificial Intelligence (AI) technology present numerous opportunities in vocational education, particularly in the hospitality sector. Front office is a department studied by Hospitality Students, however many educational institutions face challenges in providing authentic front office training, whether due to limited access to actual hotel environments, budget constraints, or a lack of opportunities to interact directly with guests. This study proposes a conceptual design of utilizing AI as an interactive virtual guest in an educational game learning application for front office training. The concept also integrates speech recognition as the form of communication with the AI virtual guest to create a realistic and interactive learning experience. The model is designed to support independent and repetitive practice through various guest scenarios such as reservations, check-in/check-out services, and providing information. A qualitative descriptive method was employed through literature review and needs analysis. The findings recommend the use of AI-based simulation as a complement to live training and as a foundation for future development of hospitality education applications. Preliminary validation using the User Experience Questionnaire (UEQ) indicates that the concept received a score of 2.0 for attractiveness, 1.82 for pragmatic quality, and 1.72 for hedonic quality, which are in the category of Positive. These results suggest that the application concept could serve as an alternative solution for vocational learning by offering a simulated experience that closely resembles real-world front office operations.